Reconceptualizing Presentation Pedagogy in EFL Contexts: A Multimodal Communication Approach - Fatwassani, Rezza; El-Muslimah, Aisyah Hafshah Saffura (Universitas Mathla'ul Anwar Banten, 2025)
This article explored the reconceptualization of presentation pedagogy in English as a Foreign Language (EFL) contexts by integrating multimodal communication strategies. Grounded in multimodal theory and communication style frameworks, the study investigated how combining linguistic, visual, aural, gestural, and spatial modes enhanced students' presentation competencies. Using a mixed-methods research design involving classroom observations, video analyses, and survey data, the study focused on sixth-semester EFL students at Universitas Islam Negeri (UIN) Walisongo Semarang. The findings revealed that students who employed multimodal strategies performed more effectively, displaying increased clarity, engagement, confidence, and audience interaction. The article argued for a pedagogical shift in EFL presentation instruction, emphasizing the need to embed multimodal competence in curricula to meet the communicative demands of contemporary global contexts.